(3GdJPcQI GdfUjQjI (B_ (3aj Yde GdgjFIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3GdeOQSI GdQTjOjI s)
(3ChdgG (B:s
(3GdMeO ddg eajV GdNjQ hedge GdUhGH fQjO Cf fhQ LedkG ef Yde GdgjFI JPcQI dHYV GdCMHGH adfhQO eG bUOfGg ai aUhd jTJed YdjgG CQHYI CHhGH s
(3BNQgG (B:s
(3hgh HYO GdKhGHJ ef eQcR GdCQV acGf NeSI hYTQjf Cda Cda hCQHY eFI , hGKfi YTQ Cda hKeGfi eFI hJSYI hJSYjf aQSNkG hdfNJe GdcJGH gGgfG MGeOjf ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG QShe gfOSjIs
(3cJHJ Hbde eged GdfbW bdjdkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
Keywords: (3Gdadcs